One lithium level >1.0 mmol/L causes an acute decline in eGFR: findings from a retrospective analysis of a monitoring database. Issue 11 (7th November 2014) - Kirkham, E; Skinner, J; Anderson, T; Bazire, S; Twigg, M J; Desborough, J A
Abstract : Objectives: Lithium is a mainstay of bipolar disorder treatment, however, there are still differences in opinion on the effects of lithium use on renal function. The aim of this analysis was to determine if there is an association between short-term exposure to various elevated lithium levels and estimated-glomerular filtration rate (eGFR) at ≤3 months, 6 months (±3 months) and 1 year (±3 months) follow-up. Setting: Norfolk-wide (UK) lithium register and database. Participants: 699 patients from the Norfolk database. Primary outcome measures: eGFR change from baseline at ≤3 months, 6 months (±3 months) and 1 year (±3 months) after exposure to a lithium level within these ranges: 0.81–1.0 mmol/L (group 2), 1.01–1.2 mmol/L (group 3) and 1.21–2.0 mmol/L (group 4). The reference group was patients whose lithium levels never exceeded 0.8 mmol/L. Results: Compared to the reference group, groups 3 and 4 showed a significant decrease in eGFR in the first 3 months after exposure (p=0.047 and p=0.040). At 6 months (±3 months) postexposure group 4 still showed a decline in eGFR, however, this result was not significant (p=0.298). Conclusions: These results show for the first time that a single incident of a lithium level >1.0 mmol/L is associated with a significant decrease in eGFR in the following 3 months when compared to patients whose lithium levels never exceeded 0.8 mmol/L. It is still not known whether the kidneys can recover this lost function and the impact that more than a single exposure to a level within these ranges can have on renal function. These results suggest that lithium level monitoring should be undertaken at least every 3 months, in line with current UK guidelines and not be reduced further until the impact of more than one exposure to these lithium levels has been fully established.